The effect of robotics on six graders ' academic achievement, computational thinking skills and conceptual knowledge levels - Kert, Serhat Bahadir; Erkoc, Mehmet Fatih; Yeni, Sabiha (ELSEVIER SCI LTD, 2020)
This study compared the pedagogical effects of educational robot development and the block based programming perspectives, which are used in programming education, on middle school students. Its participants were 78 sixth graders. Considering the students' preferences, 38 students were assigned to the experimental group, which studied with robotics (Lego EV3) sets, and 40 students were assigned to the control group, which studied with block-based programming environment (Scratch). All the topics of the programming unit, which are shown in the methods section, were taught to both groups for 10 weeks using the two different approaches. The change created by the implementation between the groups was tested for academic achievement, computational thinking skill efficacy perceptions, and conceptual knowledge levels. The results indicate that educational robotics develop middle school students' academic achievement and computational thinking skill efficacy perceptions more effectively than block-based programming environments. The connections between the concepts of the students who did robotics were also found to be more solid than those who worked with block-based software.
Keywords: Programming education; Robotics; Block-based programming; Computational thinking; Conceptual knowledge level; EDUCATIONAL ROBOTICS; Education & Educational Research